HABITAT SUITABILITY AND ZONING ANALYSIS FOR GREEN TURTLE Chelonia mydas IN THE MARINE CONSERVATION AREAS OF PANGUMBAHAN TURTLE PARK, SUKABUMI - Yusuf Arief Afandy; Fredinan Yulianda; Syamsul Bahri Agus; Lucy Peter Liew (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
This study reviews the suitability of habitat for the green turtle in the Pangumbahan Turtle Park. The purpose of this study is to evaluate the existing zoning system and to provide recommendations of alternative zoning approach based on ecological suitability turtle habitat. Observations and fieldwork were undertaken throughout the coastal area of Pangumbahan from January to June 2015 by collecting data which include nesting site for turtles, sand temperature and moisture content, width of the beach, surface slope of the beach, vegetation cover, seagrass and secondary data. Methods of data analysis consists of suitability analysis with the spatial approach using Geographic Information System. The results of the analysis of overlay method were classified into three classes of suitability, which include very suitable covering 6,91 hectares, suitable covering 14,60 hectares and less suitable covering 37,21 hectares. The current existing zones needs to be revised using the recommended zoning system. As an implementation of the findings from this study as well as to effectively manage the conservation area based on the green turtle ecology, it is highly recommended to do a zoning system which is based on the principal of the green turtles habitat suitability to ensure the sustainability of the green turtle within the conservation area. This will ensure the zoning system suits the green turtles’ characteristics hence enabling each of the zones to effectively functioning.